Analisis Kebutuhan Petani sebagai Dasar Perancangan Prototipe Aplikasi Penjualan Karet Berbasis Mobile dengan Pendekatan Rapid Application Development (RAD) di Desa Lubuk Karet - Zidan Nurgholis; Tata Sutabri (Repeater : Publikasi Teknik Informatika dan Jaringan, 2025)
Lubuk Karet Village has great potential in rubber production. However, the rubber sales process is often faced with various obstacles, such as difficulty in determining the right price and lack of transparency in transactions. This study is an analytical study using a qualitative approach. The aim is to analyze and design a prototype of a rubber sales application. This study uses questionnaires and interviews as the main data to answer research questions. The output of this study is the identification of problems and concerns of farmers related to how to calculate market prices, difficulties in recording transaction history, and minimal transparency of information regarding selling prices in the wider market. Then the second finding is regarding the prototype design of a prospective rubber sales application which will later be further developed by researchers. From the results of the analysis in this study, it is hoped that there will be further development of the application with farmer data entry features, rubber price calculations, and transaction tracking. It is hoped that this application can provide convenience for farmers in selling their crops, increase farmers' income, and provide transparent information regarding market prices. In addition, this application can also be a promotional media for local rubber products.